A new method for detecting dark Matter and explaining formulas which describe fluid matter - Alvandi, Rezvan (International Journal of Scientific Research and Management (IJSRM), 2023)
Nowadays there is a new challenge among scientists, all of us know dark energy spreads the universe by constant index, but the big question is whether the universe expanding without stopping. I am not agreeing, because on the other side, we have dark matter and we know the force of dark matter and dark energy are opposite of each other. In this article, it has been tried to explain how to detect dark fluid and made an effort to find a formula that describe the relationship between dark matter and dark energy or totally dark fluid. Throughout the history, many scientists had the idea to estimate the behavior of dark matter by the means of time, it means they desired to see what is the effect of time on the movement of dark fluid and influence of it on expanding and diminishing physical universe. Cosmology, attached to the theory of dark matter and dark energy, elaborates that both of them are in a single framework and they are not separated into ptomaine. In the last section I added time to predict dark fluid treatment by passing time. To pursue this goal, at first an experiment was designed in which by assist of cigarette smoke and electrical light, the behavior of dark fluid was observed by the author. Then, by means of quantum physic equations and adding time as a stable factor to quantum physic equation, a model and formula was coined by which it was possible to show dark fluid movement. It is very significant to state that this final formula was not completely accomplished due to the fact the gravity of black hole was not regarded in this experiment. Asan important factor, by help of cosmic noise, voyager program of NASA, information theory is related to lost galaxy information.